Argentina : First Review under the Stand-By Arrangement; Inflation Consultation; Financing Assurances Review; and Request for Rephasing, Augmentation, Waivers of Nonobservance and Applicability of Performance Criteria, and Modification of Performance Criteria-Press Release; Staff Report; and Staff Supplement. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses Argentina's First Review Under the Stand-By Arrangement (SBA), Inflation Consultation, Financing Assurances Review, and Requests for Rephasing, Augmentation, Waivers of Nonobservance and Applicability of Performance Criteria. All performance criteria and the structural benchmark for end-June were met. The authorities have proactively recognized that restoring stability in Argentina will require a significant reshaping of their policy program and have requested changes in the nature of IMF support under the SBA. The authorities are forcefully strengthening their policy program by eliminating the primary fiscal deficit in 2019 and targeting a primary surplus in 2020. The IMF staff supports the authorities' request to modify the program supported by the SBA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet